Potency and stability of compounded cyclophosphamide: a pilot study. (30th March 2016) - Robat, C.; Budde, J.
Abstract: Compounding of drugs for use in veterinary oncology is becoming increasingly common. We obtained 15 mg cyclophosphamide capsules from five different compounding pharmacies and performed potency analyses at two time points, as well as stability at 60 days. Potency results for four out of five and zero out of five (4/10) samples analysed were inadequate. Stability at 60 days was acceptable for all but one sample. This pilot study raises several important points of concern when compounding chemotherapy in dogs and cats. Further studies are necessary to solidify this data. Collaboration between pharmacists, veterinarians and regulatory bodies is needed to ensure safe and accurate delivery of compounded drugs to client‐owned animals.